Effect on the white cell count of contaminating cerebrospinal fluid with blood. Issue 5 (May 1981) - Osborne, J P; Pizer, B
Abstract : Retrospective analysis of heavily blood-stained cerebrospinal fluid shows that there are fewer white cells found in this fluid than would be expected by calculations using the peripheral blood red to white cell ratio. This phenomenon may disguise a true leucocytosis.